Audit committee characteristics and tax avoidance: Evidence from an emerging economy - Van Cuong Dang; Quang Khai Nguyen (Cogent Economics & Finance, 2022)
This study aims to examine the impact of the characteristics of the audit committee on tax avoidance in Vietnam. The article uses data of non-financial firms listed on the Ho Chi Minh City and Ha Noi Stock Exchange over the period 2010-2019. By using the FEM and SGMM estimation for panel data, the empirical results show how the characteristics of the audit committee affect tax avoidance differently. Specifically, we find that the size of the audit committee has a positive correlation to tax avoidance, while the proportion of female members, financial and accounting experts of the audit committee can constrain tax avoidance behaviors. Our finding provides some important implications for listed firms to enhance the role of the audit committee in constraining tax avoidance behavior.
Keywords: G32; H25; H26; 330; audit committee size; audit committee independence; gender; financial experts; tax avoidance